Three-dimensional nanoporous heterojunction of CdS/np-rGO for highly efficient photocatalytic hydrogen evolution under visible light. (25th March 2023) - Yuan, Chunyu; Lv, Huijun; Zhang, Yujin; Fei, Qian; Xiao, Dongdong; Yin, Hongfei; Lu, Zhen; Zhang, Yongzheng
Abstract: Properly engineered heterojunction photocatalysts warrant a more effective way to facilitate the separation of photoexcited electron-hole pairs and consequently bolster the photocatalytic hydrogen evolution performance. Herein, 3D bicontinuous nanoporous reduced graphene oxide (np-rGO) is served as a free-standing supporting matrix for the anchorage of CdS nanoparticles to obtain the highly efficient photocatalysis system for hydrogen production. The bicontinuous internal ligament and open nanopores in 3D nanoporous heterojunction are conducive to multiple reflecting and scattering of the incident light, leading to improved light absorption and utilization capacity. Moreover, the construction of p-n heterojunction with staggered band alignment is achieved in CdS/np-rGO to accelerate the transport of photo-excited carriers. The constructed CdS/np-rGO p-n heterojunction achieves a corresponding hydrogen generation rate of 2171.23 μmol g −1  h −1, which is 3.6 times in comparison with bare CdS. DFT calculations also indicate the preferable photocatalytic performance of CdS/np-rGO could be assigned to the ideal interfacial charge rearrangement on the heterointerface, which optimizes the H* adsorption kinetic energies and leads to a remarkable enhancement in the charge separation efficiency. It is anticipated this work could provide new sight for making the best usage of sunlight to produce solar fuel. Graphical abstract: Image 1 Highlights: 3D free-standing nanoporous heterostructures are prepared. P-n junction with staggered band alignment promotes charge separation. Ideal interfacial charge rearrangement optimizes the H* adsorption free energies.